Production of cookies with partial substitution of wheat flour for pole bean and castilla bean flour - Quiroz Ponce, Freddy (2024)
Background: The substitution of flours was proposed to determine which is more suitable for cookie production, utilizing the processing of pole and castilla beans. Methods: A randomized design (DCA) was used to create 8 treatments and a control, applying substitution percentages of 10%, 20%, 30%, and 40%. Treatments were sensorially evaluated by a panel of 30 untrained judges, followed by statistical analysis. Results: The treatment containing 40% castilla bean flour and 60% wheat flour was best rated with the following means: 3.70 in color, 3.70 in aroma, 3.77 in taste, and 3.83 in texture. Physicochemical tests resulted in carbohydrate content of 53.81%, ash content of 0.93%, fiber content of 1.90%, fat content of 23.15%, moisture content of 10.03%, protein content of 12.08%, and a pH of 6.74. The product did not exceed the maximum limits set by the INEN 2085 standard. Conclusions: It was identified that the combination of castilla bean and wheat flour is beneficial for enhancing the nutritional contribution in cookie production, rendering them suitable for human consumption.